A langasite surface acoustic wave wide-range temperature sensor with excellent linearity and high sensitivity - Hongsheng Xu; Hao Jin; Shurong Dong; Jinkai Chen; Xinyu Song; Weipeng Xuan; Lin Shi; Shuyi Huang; Pengjun Zhang; Jikui Luo (AIP Advances, 2021)
Langasite (LGS) surface acoustic wave (SAW) temperature sensors have a large second order temperature coefficient of frequency, which leads to their non-linear and non-monotonic responses in a wide temperature range and possibly makes the measured temperatures non-unique for a specific sensor response. Here, we propose a high-temperature Pt/LGS SAW sensor with linear frequency–temperature behavior in a wide temperature range, which was fabricated on a LGS (0°, 138.5°, 72°) substrate. The sensor has a single acoustic mode, but dual resonances with similar second- and third-order temperature sensitivities that were utilized for achieving a linear frequency–temperature response by a method of difference. A linear relationship between the measured sensor output (Δfm21) and temperature was obtained in the range of −60 °C to 700 °C, consistent with the theoretical analysis. The sensor has a high sensitivity of −167 ppm/K for the whole temperature range. All the results demonstrated exciting prospects of the sensor for wide temperature monitoring in harsh environments.